Genotype and age of industrial plant Jatropha curcas L. affect physico-chemical properties of seed oil - Islam, A. K. M. Aminul; Yaakob, Zahira; Ghani, Jaharah A.; Alareefy, Azza; Abdulsalam, Nisreen M.; Khateeb, Najla A.; Zidan, Nahla; Abdelazi, Mahmoud A.; El Sabagh, Ayman; Sakran, Mohamed I.; Omran, Awatif; El Askary, Ahmad; et al. (Frontiers in Energy Research, 2022)
Jatropha curcas, has been established as a plant whose seeds contain a relatively high percentage of oil that is suitable for biodiesel production, among other industrial applications. Seed oil properties of J. curcas may vary depending on soils, age of plant, genotype of the plant, and agro-climatic conditions of a specific geographical region. Studies under such conditions have not yet been conducted. The present study was aimed at investigating the effects of genotype and age of the plant on the physicochemical properties of its seed oil. The seed oil was extracted using n-hexane as a solvent in the Soxhlet extraction apparatus from seed kernel collected from different genotypes and plants of different ages. Oil content in the kernel ranged from 49.78–53.75% (w/w) among the seed samples depending on genetic materials and plant age. The oil content showed very little but significant differences in density and specific gravity among the samples. The highest free fatty acid (FAA) was produced by the kernel oil of 3-year-old plants (7.78%), and 7- and 10-year-old plants gave the lowest FAA (1.26 and 1.31%, respectively). The kernel oil of 7-year-old plants produced the highest iodine value (93.60 mg/g oil) and the kernel oil of 3-year-old plants produced the lowest iodine value (61.10 mg/g oil). Kernel oil of 10-year-old plants gave the lowest (172.98 mg KOH/g) saponification value and 4-year-old Hybrid-3 gave the maximum value (209.97 mg KOH/g oil). The seed oil of Jatropha accessions showed very little difference (39.88–40.85 MJ/kg) for high heating values irrespective of their age. On the other hand, the cetane number varied from 55.32 to 59.58 in the oil samples. The age of plant and seed sources had a significant effect on seed oil content and the physio-chemical properties of Jatropha.